Selective upper segment ureteral reimplantation for duplicated urinary tract using vesicoscopic access - A. V. Pirogov; V. V. Sizonov; M. I. Kogan (Вестник урологии)
Introduction. During the correction of ureterovesical junction (UVJ) obstruction of the upper segment of the duplicated upper urinary tract (DUUT), the healthy part of the DUUT may be involved around surgery area. Therefore, it risks damage to the complex or even complete loss of the renal unit.Objective. To evaluate preliminary results for the repair of upper segment obstruction of duplicated upper urinary tract without involvement of the unaffected segment of the renal unit using vesicoscopic access.Materials & methods. Since 2022, selective ureteral reimplantation of the upper segment of the DUUT according to Cohen using vesicoscopic access (VSA) has been performed in three children. A boy aged 23 months, a girl aged 18 months, and a boy aged four months had unilateral ureterohydronephrosis (SFU grade IV) of the upper segment of the DUUT with ectopy of the ureteral orifice into the urethra. All patients underwent laboratory tests, ultrasound, intravenous urography, retrograde micturition cystography, CT scans. Urinary tract infection, increasing hydronephrosis and dilation of the DUUT were the indications for surgery. Surgery efficacy was evaluated by ultrasound and urine analyses.Results. All surgeries were completed using VSA devoid for conversion. Surgery time was between 110- and 150-min. Blood loss was 10 ml. Postoperative complication was observed in one patient represented by dynamic intestinal obstruction with subsequent anaemia. The reason was inadequate function of the urethral catheter in the early postoperative period, which was unrelated to the core features of the technique. The postoperative stay ranged from 8 to 14 days. Absence of pyelonephritis, significant reduction in the grade of upper urinary tract dilation were observed according to the postoperative examination in all patients within 3 to 6 months after surgery. We did not detect pathological changes in the lower segment of the affected DUUT in any patient postoperatively.Conclusion. Selective ureteral reimplantation of the upper segment of the DUUT according to Cohen using VSA is a feasible and safe procedure that can effectively relieve obstruction of the upper half of the DUUT without surgical involvement of the unaffected part.